Development of Ocular Inserts Based on Import Substituted Poloxamer Emuxol 268 - E. O. Bakhrushina; A. R. Turaeva; D. R. Zhalyalova; D. A. Klimov; N. B. Demina; I. I. Krasnuk (Разработка и регистрация лекарственных средств, 2024)
Introduction. Emuxol-268 (JSC "NIOPIK", Russia) is a block copolymer produced in Russia with similar in physicochemical and biological properties to poloxamer Kolliphor® P 188 (Pluronic F68) manufactured by BASF, USA. However, a comparison of the properties of natural polymers to assess the prospects of their dosage forms has not been carried out before.Aim. The aim of the study was to demonstrate the interchangeability of auxiliary components using the example of the development of an ophthalmic drug insert by comparing the results of testing the dosage form in terms of such quality parameters as elasticity, thickness, mucoadhesion, pH, biodegradation time and irritation test (hen’s egg-chorioallantoic membrane test, HET-CAM test).Materials and methods. Poloxamers Emuxol 268 (JSC "NIOPIK", Russia) and Kolliphor® P 188 (BASF, Germany), hydroxyethyl cellulose (Natrosol™ 250 HHX, Ashland Global Holdings Inc., USA), and glycerol (LLC "Tulskaya Pharmfabrika", Russia) were used in the experiment. Elasticity, thickness, mucoadhesion, pH, biodegradation time, HET-CAM test were used as screening methods to identify the benefits of the composition.Results and discussion. Experiment results proved that the use of a domestic analogue makes it possible to create an ocular insert with improved quality parameters. The difference in the elasticity index of the inserts differs by 1.3 times, mucoadhesion – 1.7 times, biodegradation time – 2.5 times. In this connection, it can be assumed that an insert based on a domestic polymer contributes to an increase in the time of contact with the eye surface, thereby providing a prolonged effect of the drug and improving its bioavailability. The results obtained may be due to the difference in the average molecular weight of the hydrophobic polyoxypropylene part, which is 2600 Da for Emuxol 268 and 1800 Da for Kolliphor 188. The HET-CAM method showed the same results of the two compositions, both compositions do not have an irritating effect.Conclusion. Summing up, the only analogue of Kolliphor® P 188 available on the Russian pharmaceutical market – Emuxol-268 of JSC NIOPIK is a promising substance for replacement in the development of ophthalmic dosage forms. Despite the differences in physicochemical properties of the domestic block copolymer in comparison with the replaced poloxamer 188, its introduction into placebo inserts gave improved results in terms of quality indicators, which was revealed during a biopharmaceutical analysis.